Correlations between microstructure of α‐row nuclei and polymorphism of shear‐induced iPP/carbon fiber cylindrite. Issue 7 (12th February 2019) - Zhao, Jing; Zhang, Jihai; Jing, Mengfan; Sui, Guopeng; Liu, Dingyao; Wang, Ke; Fu, Qiang
ABSTRACT: Herein, we reported the formation mechanism of hybrid crystalline (cylindrite) in isotactic polypropylene (iPP)/carbon fiber ( CF ) via pulling a CF within the iPP melt. The α‐row nuclei layer closely attached to the surface of CF acts as a self‐nucleation site, rather than a heterogeneous nucleation one, to grow cylindrites. As a result, the polymorphic feature of iPP/ CF cylindrite is significantly influenced by the microstructure of α‐row nuclei. With decreasing crystallization temperature ( T c ), the polymorphic cylindrite changes from pure α‐form to mixed α‐/β‐form and to β‐rich form. The main characteristics of this change include: (a) the outlines of α‐row nuclei layer correspond to wave‐like, saw‐like, and straight lines; (b) the orientation level of iPP molecules in the α‐row nuclei layer become higher; (c) the α‐lamellae rearrange from loose to compact; and (d) the distance between the growth sites of β‐sectors and the surface of CF is evidently longer than in the case of α‐sectors. Moreover, this study provides a guideline for developing the interfacial enhanced iPP/ CF composites through manipulation of polymorphic structure in cylindrites. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 368–377 Abstract : The correlation between the α‐row nuclei and shear‐induced iPP/ CF variable cylindrite (pure α‐cylindrite, mixed α/β‐cylindrite, and β‐rich cylindrite) was systematically established by comparing the detailed microstructure. The systematical growth processes of shear‐induced cylindrites with different crystalline temperatures are illustrated. Furthermore, it was concluded that the polymorphism of cylindrite is strongly dependent on the orientation and packing density of the fibril lamellae in the α‐row nuclei.